THE CONCEPT OF LEGAL IDEOLOGY AND ITS PLACE IN THE THEORETICAL AND LEGAL KNOWLEDGE - Ergashev Omonillo (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The paper discusses the theoretical approaches to the social-philosophical analysis of a phenomenon of ideology. In social-humanitarian knowledge the concept “ideology” is used in several meanings as a specific belief, as the belief based on false knowledge of the social and as a set of ideas in the various spheres - from scientific knowledge to religion and daily views on appropriate behavior, not depending on that whether these beliefs are true or are false. This paper examines these three approaches that demand a historical retrospective show of the genesis of the concept of “ideology”.